2015
DOI: 10.1260/1747-9541.10.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Sprinting Activities and Distance Covered by Top Level Europa League Soccer Players

Abstract: This study presents a detailed analysis of sprinting activities and distance covered by professional soccer players in two seasons of the Europa League competition. The investigation considered such variables as the mean sprinting distance covered, duration of the rest pause between sprinting activities and maximal running speed recorded during the match. The study involved 147 soccer players participating in 10 matches played at one ground in the 2008–2009 and 2010–2011 Europa League seasons. Players' perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
73
4
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 27 publications
14
73
4
5
Order By: Relevance
“…14 Secondary factors affecting external workload include the style of play and team formation. 22,20 The evolution concerning style of play within professional football has been suggested by Di Mascio and Bradley, 14 whom produced conclusions which demonstrate an increased distance covered by contemporary English Premier League players (11 km) compared to those in the original First Division (8.2 km) observed by Reilly and Thomas. 23 The increase in 2.8 km supports the physical demands of football increasing with every position involved in defensive and offensive phases across a match.…”
Section: Positional Variables Affecting External Workloadmentioning
confidence: 94%
See 1 more Smart Citation
“…14 Secondary factors affecting external workload include the style of play and team formation. 22,20 The evolution concerning style of play within professional football has been suggested by Di Mascio and Bradley, 14 whom produced conclusions which demonstrate an increased distance covered by contemporary English Premier League players (11 km) compared to those in the original First Division (8.2 km) observed by Reilly and Thomas. 23 The increase in 2.8 km supports the physical demands of football increasing with every position involved in defensive and offensive phases across a match.…”
Section: Positional Variables Affecting External Workloadmentioning
confidence: 94%
“…Conflicting research debates the total distance travelled throughout a match; the concluded distance players cover is 8-12 km, with distances at elite levels reaching 14 km. 20,16 Collective studies, conclude midfielders performing the largest total distance in comparison to other playing positions. 3,10 External midfielders previously recorded distances covering 11990+776 m whilst central midfielders recorded distances of 12027+625 m throughout the duration of a 90-minute match.…”
Section: Positional Variations In External Workloadmentioning
confidence: 99%
“…Subjected by the present study as a specific key adjustment of player technique referred to its component skill-related fitness developments (Ronald, 2009). Agreed by Andrzejewski, et al, (2015) via the player capacity to recover from high-intensity efforts or fatiguing actions in repeating game-related skills efforts ISSN 1993-7989 (print). ISSN 1993-7997 (online).…”
Section: Introductionmentioning
confidence: 99%
“…Agreed in the case of this study, within the maximal aerobic speed (MAS). As a conventional device to establish the specific player training and to allowing trainers to monitor training loads more accurately (9). Aimed at the present study, through levels of (MAS) as a protocol to test their relations with skills fitness abilities.…”
Section: Introductionmentioning
confidence: 99%